CONSTRUCTION OF INVARIANT CONTROL SYSTEMS OF MULTI-MODE OBJECTS - Кучерук, Н. В. (Science-based technologies, 2016)
The use of automatic control systems allows to expand the possibilities of the use of technical devices. One of the solutions of optimal problems of the equation in terms of continuous use of technical systems with constant coefficients are the use of piecewise constant functions. A specific feature of the systems under consideration, consisting in the fact that the shape of the control action does not depend on the shape of the vector control algorithm output control signal. This allows the algorithm to generate the control action, providing the specified quality criteria, using different state variables of the control object. Therefore, the aim of the article is an opportunity to show the invariance of the management of quality criteria for Class 1 piecewise negative objects (multi-mode) in the synthesis of optimal control algorithms by the method of P-functions. The solution of this problem allows the synthesis of a control system under conditions of incomplete information about the state of the object to implement an autonomous and invariant control with an additional stabilizing effect.